KNOWLEDGE MANAGEMENT OF FARMERS’ BEHAVIOR AND THEIR REIATIONSHIP TO SCIENTIFIC SOURCES OF INFORMATION AND RECOMMENDATIONS TO REDUCE THE EFFECT OF CHEMICA FERTIIZERS AND PESTICIDES ON ENVIRONMENT AND HUMAN HEALTH - Salih, Majeed Hadi (Diyala Agricultural Sciences Journal, 2020)
The research aims to Identify the level of managing farmers' knowledge and their relationship to scientific sources of information and recommendations to reduce the effect of chemical fertilizers and pesticides on the environment and human health, as well as determine the relationship Between the dependent variable and the studied This research was carried out in the Victory and Peace Agriculture Division of the Baghdad / Karkh Agriculture Directorate. The study population numbered (1045) farmers are registered, and the researcher selected a random sample from the study population of (160) farmers to study the chemical fertilizer axis, i.e. (15.3%), and the percentage (14.5%) of the study population was a random sample from the research community to study the axis of chemical pesticides, as the number reached (152) farmers. The questionnaire was used to collect data from farmers on a personal interview in January 2020, after all, The most important results were that the percentage of the field of chemical fertilizers was 73.75%, the field of chemical pesticides was 63.16%, and there was also no significant difference between the average levels of management knowledge of the behavior of farmers and the fields of study of fertilizers and chemical pesticides, and it was found that there are problems experienced by farmers in the management of Knowledge of the behavior of farmers in the areas of research fertilizers and chemical pesticides significantly, with regard to proposals by farmers, it is good and on the government agricultural agencies and support activating the role of agricultural extension in the field of fertilizers and chemical pesticides to change the behavior of farmers. The most important recommendations were to spread awareness among farmers and to use recommendations and scientific information in growing crops.